Prevalencia de metastrongylus metastrongiloides en cerdos faenados en el camal municipal del cantón Machala provincia de El Oro - Monar Garay, Jean Paul (2005)
An essay was carried out at the Municipal Slaughterhouse of Machala City canton in order to determine the prevalence of the parasite Metas-trongiloides in swine. From December/2002 until March/2003, a total number of 3 008 pigs were sampled, with ages ranging from younger than 12 months, from 13 to 24 months and older than 25 months. The diagnosis was done by mean of the sanitary inspection of the lungs. At the ending of this essay it was established a percentage of 4,62% of prevalence. The conclusions were as follow: a) The prevalence of Metastrongiloides in swine was 4,62%; b) from the total number of sampled animals, 139 were positive and 2869 were negative to the presence of the parasite; c) according to distribution by ages, the prev-alence was of 3,97% for animals younger than 12 months, 6,08% for animals from 13 to 24 months, and 0% for animals older than 25 months; d) with reference to strain the Landrace variety had a high prevalence: 13,33%, Duroc Mestizo 9,37%, followed by Criollos with 6,25%, Yorkshire with a prevalence of 4,62%, Duroc Jersey with 3,4% and Pietrain, the lowest with 1% of prevalence. The Hampshire variety was negative; e) In relation with sex, the prevalence in males was 3,56% and in females 5,32%, and from a total number of3008 sampled animals, 1204 were males and 43 positive, 1804 females and 96 positive; f) taking in account the precedence, the results were: Machala (4,72%), Balsas (2,49%), Santa Rosa (5,24%), Pasaje (6,04%), Tenguel (10,49%), Puerto Bolívar (3,94%), Arenillas (4,19%), Piñas (3,31%), Balao Grande (11,38%), Guabo (4,34%), Calderón (6,49%), 100 Families (10,34%), Río Bonito ( 4,54%), Jilili (10%), Santa Isabel, Azuay (100%). The zones of Ponce Enriquez, road to Loja and Perú did not register positive cases; g) According to type of explotation, the animals in homemade "chancheras" or "chiqueros" resulted more affected by the parasitosis with a percentage of 8,90%, followed by free animals with 2,46% and animals in swine farms with 0,52%.